A Study on Common Facilities Management in Pagoh Campus Residential College, Universiti Tun Hussein Onn Malaysia - Binti Sobri, Nur Syafika; BIN ROSLI, Ts. Dr. MOHD ARIF; ABDUL RAHMAN, Ts. MOHD FAHMI (Progress in Engineering Application and Technology, 2025)
This study assessed facilities management at Pagoh Campus Residential College, UTHM, through feedback from 290 residents collected via structured questionnaires. Demographic data indicated that the majority of respondents were female (61.7%), with 52.1% having resided at the residential college for 2 to 4 years. The study identified key issues, including a non-functional water machine in Block A15, delays in laundry service repairs, and communication problems between residents and the maintenance team. A total of 55.5% of residents reported facility damages, with 44.8% of repairs completed within 1-2 weeks, while a small percentage (1.1%) experienced repairs taking more than four weeks. Residents were generally satisfied with the facilities provided, particularly the ventilation system, electrical appliances, and furniture adequacy. However, they also suggested improvements, such as upgrading the audio system in the Multipurpose Hall, adding more power outlets, and improving Wi-Fi connectivity in learning rooms, as well as improving the layout and furniture in the Student Mart. Maintenance response times were also a concern, with 45% of respondents expressing satisfaction with repair times. This study recommends improving communication channels, implementing a resident feedback system, encouraging responsible facility usage, and ensuring timely maintenance. These improvements aim to enhance resident satisfaction and the effectiveness of facilities management, addressing current issues and future needs to ensure better living conditions at the residential college.